America and the Pacific century : trade conflict or cooperation. - AHO, C. Michael (1993)
Reviews how America embarked upon its current trade policy with its mixed signals that jeopardize American credibility on trade issues. Identifies three factors on which US foreign economic policy towards the Asia-Pacific depends: the implications of NAFTA; the outcome of the Uruguay Round of multilateral trade talks (GATT); and, the state of US-Japan relations.